Pengaruh Kepercayaan Konsumen dalam Marketplace dan Kualitas Layanan Digital terhadap Keputusan Pembelian UMKM Fashion - Aulia Miftah Az-Zahra (CV. ITTC INDONESIA, 2026)
The growth of digital s has changed consumer behavior in purchasing fashion products online. This study aims to analyze the influence of consumer trust and digital service quality on purchasing decisions of fashion SMEs in s through a literature review approach. The findings indicate that consumer trust reduces transaction risks, while digital service quality, including seller responsiveness, accurate product information, and reliable delivery, positively influences purchasing decisions. The study implies that fashion SMEs should improve information transparency and digital service quality to strengthen their competitiveness in marketplace.